FUNCTIONING ADRENOCORTICAL ONCOCYTIC CARCINOMA: A RARE VARIANT - Kannesan, Dineash Kumar; Roslan, Teh Roseleen Nadia; Yahaya, Norhayati; Hassan, Aniza; Isa, Junaidi Awang (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Adrenocortical oncocytic carcinoma (AOC) is a rare histopathological variant of adrenocortical carcinoma (ACC) that is mostly non-functional that are discovered incidentally or present with vague abdominal pain. Functioning AOCs are extremely rare. CASE We report the case of a 62-year-old Siamese female who presented with progressive left-sided abdominal pain. Computed tomography demonstrated a huge mass over the left upper retroperitoneal region. Biochemically, the patient had possible autonomous cortisol secretion. Left adrenalectomy was successful with R0 resection, histological examination revealed AOC (based on LinWeiss-Biscelgia score) with Ki-67 of 10% and she was staged as ENSAT Stage 2. She is under periodic imaging surveillance. Nearly 3 years after complete resection, there was no evidence of recurrence or metastasis clinically and radiologically and her cortisol status reverted to normal. CONCLUSION In summary, we describe here an extremely rare case of functioning AOC which differs clinically from conventional ACC and showed a more favourable prognosis.